Kepemimpinan Kepala Sekolah dan Kinerja Guru Honorer Sekolah Dasar: Tinjauan Literatur Integratif - Romi Oriza (Lembaga Yasin AlSys, 2026)
Honorary teachers play an important role in maintaining the continuity of primary education services, but their performance remains vulnerable because of limited compensation, uncertain employment status, unequal access to professional development, and the organizational climate of schools. Meanwhile, evidence regarding leadership mechanisms specifically relevant to honorary primary school teachers remains fragmented and more limited than research on teachers in general. This review aimed to synthesize the roles and strategies of school principal leadership in strengthening the performance of honorary teachers. The study employed an integrative literature review method through structured searches of Google Scholar, Garuda, DOAJ, Crossref, and publisher websites. A total of 21 substantive articles and two methodological references were analyzed through data extraction, thematic coding, comparison of findings, and interpretive synthesis. The review identified five main leadership mechanisms, namely clarifying work direction and expectations, implementing developmental academic supervision, providing motivational support and recognition, facilitating competency development, and creating a fair and participatory work climate. The effectiveness of these five mechanisms was determined by implementation consistency, communication quality, leaders’ exemplary conduct, proportional task allocation, and follow-up evaluation. However, because most of the analyzed studies employed correlational or qualitative designs and did not specifically focus on honorary teachers, the findings cannot be interpreted as uniform causal evidence. This review concluded that instructional, transformational, participatory, and humanistic leadership should be integrated through needs-based development, continuous supervision, equitable access to professional development, and transparent recognition systems. These findings contribute to the development of educational leadership research and provide practical implications for school principals in designing fairer, more supportive, and performance-oriented management strategies for honorary teachers.